Grocery retailing in Germany: Situation, development and pricing strategies - Roland Herrmann; Anke Möser; Sascha A. Weber (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2009)
Like many other industrialised countries Germany has experienced a powerful concentration process in food retailing. There are some issues, however, which make Germany a special case in Europe and among industrialised countries in general. This holds true in terms of market structure and concentration, market development and pricing strategies. The market share of hard discounters like Aldi and Lidl has grown continuously in recent decades and the market share of discounters in general has reached a magnitude that is well above that found in other European countries. This has led to robust price competition in German food retailing. Along with this development, it has been very difficult for inward foreign direct investment (FDI) to gain ground in the German food retailing industry. One example was the market entry by Wal-Mart which, given its initial ambitious goals, was not successful. On the other hand, German hard discounters have strongly affected outward FDI by other German food retailers. In the process of expanding into other markets abroad, these companies have had a positive impact on exporting by the German food industry. This article describes and analyses these major trends in German food retailing in detail. It is organised as follows. The structure of food retailing is described and explained in Section 2. Section 3 deals with the importance of inward and outward FDI in German food retailing. It is discussed in both sections how increased concentration in food retailing affects the marketing chain. Price competition is intense in Germany, and studies of food pricing strategies have used scanner data. Therefore a special case study in Section 4 is the analysis of food pricing strategies in Germany based on scanner-data evidence. The analysis shows that the pricing behaviour of food retailers is characterised by the every-day-low-pricing (EDLP) strategies of discounters and the high-lowpricing (HiLo) strategies of their major competitors. The main elements of pricing policies are indicative of firms' market power: repeated price discounts for major food brands, frequent changes of loss leaders, the dominant role of psychological pricing, and a strong price rigidity for all other foods which are not on special offer.
Keywords: 330; Lebensmitteleinzelhandel; Branchenentwicklung; Direktinvestition; Einzelhandelspreispolitik; Preiswettbewerb; Deutschland